2m+10-5m=6(m+2)-9m

Simple and best practice solution for 2m+10-5m=6(m+2)-9m equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2m+10-5m=6(m+2)-9m equation:



2m+10-5m=6(m+2)-9m
We move all terms to the left:
2m+10-5m-(6(m+2)-9m)=0
We add all the numbers together, and all the variables
-3m-(6(m+2)-9m)+10=0
We calculate terms in parentheses: -(6(m+2)-9m), so:
6(m+2)-9m
We add all the numbers together, and all the variables
-9m+6(m+2)
We multiply parentheses
-9m+6m+12
We add all the numbers together, and all the variables
-3m+12
Back to the equation:
-(-3m+12)
We get rid of parentheses
-3m+3m-12+10=0
We add all the numbers together, and all the variables
-2!=0
There is no solution for this equation

You can always share this solution

See similar equations:

| 0.5x-3.9=-1.9 | | 5z+4/3-(-3z-5/2)=-z+43/6 | | 7(x+3)=-21 | | 7x+2-3x+1=8x+4-x+1 | | 4z+8=7 | | (3x/2)+(7x/2)=1 | | 3x+7x=1 | | 1=100e^-0.35N | | 3x+40+2x+6=88 | | P=-x-40x2+2,240x-17,000 | | 3+7=5x | | x^2+6x+6=-5 | | 5-7x=10-2x | | 2x+16=4× | | 160-(3x+x)=0 | | 160-(3x-x)=0 | | 5a+86=4a+24 | | 4t+8=39 | | 8^(2+x)=2 | | 3(m+12)=-18 | | 5)6n+8=2n+36 | | X+8÷13-x=23 | | 10+5x3=45 | | 7n+9=n+5 | | 0.49x=7350 | | x/56=0.8 | | 73x=12x | | 43+6x+15=8x-1 | | 16=2s+15 | | 43+8x-1=6x+15 | | 2/3x+1/2x-2=x-4 | | | | |

Equations solver categories